Genome-resolved transcriptomics reveals novel PCE-dehalogenating bacteria from Aarhus Bay sediments - Chen Zhang; Tom N. P. Bosma; Siavash Atashgahi; Hauke Smidt (mSystems)
ABSTRACT Organohalide-respiring bacteria (OHRB) are keystone microbes in bioremediation of sites contaminated with organohalides and in natural halogen cycling. Known OHRB belong to distinct genera within the phyla Chloroflexota, Proteobacteria, and Firmicutes, whereas information about novel OHRB mediating natural halogen cycling remains scarce. In this study, we applied a genome-resolved transcriptomic approach to characterize the identity and activity of OHRB from tetrachloroethene respiring cultures previously enriched from sediments of Aarhus Bay. Combining short- and long-read sequencing approaches, we assembled 37 medium-quality bins with over 75% completeness and less than 5% contamination. Sixteen bins harbored RDase genes and were affiliated taxonomically to the class of Bacilli and phyla of Bacteroidota, Synergistota, and Spirochaetota, which have not been reported to catalyze reductive dehalogenation. Among the 16 bins, bin.26, phylogenetically close to the genus Vulcanibacillus (phylum Firmicutes), contained an unprecedented 97 reductive dehalogenase (RDase) genes. Of these, 84 RDase genes of bin.26 were transcribed during tetrachloroethene dechlorination in addition to RDase genes from the members of Synergistales (bin.5 and bin.32) and Bacteroidales (bin.18 and bin.24). Moreover, metatranscriptome analysis suggested that the RDase genes were likely under the regulation of transcriptional regulators not previously associated with organohalide respiration, such as HrcA and SigW, which are known to respond to abiotic environmental stresses, such as temperature changes. Combined application of genomic methods enabled us to pinpoint novel OHRB from pristine environments not previously known to mediate reductive dechlorination and to add to the current knowledge of the diversity, activity, and regulation of RDase genes.IMPORTANCEPristine marine environment is the major reservoir for naturally produced organohalides, in which reductive dehalogenation underneath plays an important role in the overall cycling of these compounds. Here, we obtain some novel OHRB genomes from Aarhus Bay marine sediments, which are phylogenetically distant to the well-documented OHRB and widely distributed across the bacterial phyla, such as Bacteroidota, Synergistota, and Spirochaetota. Furthermore, transcriptional profiles unravel that these RDase genes are induced differently, and their activity is controlled by diverse regulatory systems. Accordingly, elucidating the reductive dehalogenation of pristine marine environments substantially advances our understanding of the diversity, phylogeny, and regulatory variety of dehalogenating bacteria contributing to the global halogen cycle.